Chronic pericardial effusion in the setting of pericardial capillary haemangioma: a case report and review of the literature. Issue 1 (6th March 2018) - Seitz, Andreas; Ong, Peter; Backes, Maik; Mahrholdt, Heiko
Abstract: Introduction: Cardiac haemangiomas are rare vascular tumours of the heart accounting for less than 5% of benign primary cardiac neoplasms. They are sometimes diagnosed incidentally, since patients can be asymptomatic. The clinical presentation in symptomatic patients, however, is variable, depending on size and exact localization of the tumour. Although cardiac haemangiomas have been reported everywhere in the heart, those localized in the pericardium are extremely rare. Case presentation: A 48-year-old female patient with a history of pericardial effusion and pneumonia was admitted to our hospital with progressive dyspnoea on exertion. Echocardiography demonstrated recurrence of pericardial effusion with 'swinging heart'. Further investigation by computed tomography, cardiac magnetic resonance imaging and coronary angiography revealed a hypervascular pericardial mass with typical 'tumour blush' after contrast injection. The tumour could be resected in toto by open heart surgery, and histological evaluation confirmed the diagnosis of a pericardial capillary haemangioma. There were no signs of recurrence of neither the pericardial effusion nor the tumour during follow-up. Discussion: We here report a very rare case of a pericardial haemangioma in the adult which was diagnosed by multi-modality workup of recurrent pericardial effusion. This case illustrates that in the setting of chronic pericardial effusion non-inflammatory and non-malignant causes should be taken into account.